Reality Stems From Modality: Stereotype Threat Effects of a STEM Game in Augmented and Virtual Reality - Ratan, Rabindra; Boumis, Josephine K.; Kuang, Sarah; Gambino, Andrew; Huang, Kuo-Ting (Frontiers in Virtual Reality, 2021)
This study examined the relationship between stereotype threat, game modality (augmented reality, virtual reality), and stereotypic beliefs about STEM fields. Results of a 2 [modality] x 2 [stereotype threat] factorial, between-subjects experiment with women participants (N = 64) suggest that gender stereotypes primed before playing the STEM game in AR induced stereotype threat, but induced stereotype reactance in VR. Specifically, for participants who played in AR, the stereotype-reinforcing prompt (compared to a counter-stereotype prompt) was associated with worse STEM-game performance, which mediated an increase in stereotypical beliefs about women in STEM. Conversely, for participants who played in VR, the stereotype-reinforcing prompt was associated with better STEM-game performance and more positive (i.e., counter-stereotypic) beliefs about women in STEM, though without mediation. These findings support the claim that stereotypes triggered in a STEM-gaming context have the potential to reinforce stereotypes in STEM fields. Researchers and practitioners should consider the implication that VR is potentially more male-stereotyped than AR, while AR makes stereotyped identity characteristics more accessible than VR.